Critérios de seleção e indicadores de desempenho para contratação de serviços logísticos: um estudo de casos múltiplos com embarcadores e operadores logísticos - Galo, Nadya Regina (Universidade Federal de São Carlos, 2014)
A company doesn t operate singly in the market, because it is involved in a chain of buyers and suppliers, from which depends its operational efficiency. Thus, the choice of a partner requires the fulfillment of a number of requirements to ensure that business objectives will be not affected by inadequate supply. In this context, supplier selection can be an important process for an organization that wishes to evaluate the alternatives according its preference criteria for contracting services. However, certain criteria may present difficulties in measuring and to define indicators that can compose each criterion can allow the performance measurement of each supplier, adding objectivity to the process. The objective of this research was to identify and analyze which criteria supplier selection are used for hiring logistics service providers (LSPs) and what are the indicators used to assess the performance of this partner, in a group of companies in the retail. For this, we used the method of case study in five companies, four shippers and one 3PL. This is an exploratory qualitative research and the technique used was the direct intensive research using semi-structured questionnaires. Thus, were identified and analyzed the selection criteria and performance indicators used by companies to selection and evaluation of LSPs. The analysis allowed characterizing the selection of suppliers of these companies and performance measurement, as well as some specific features. As a result, it was observed that companies can point which criteria are relevant for the selection of LSPs and they have indicators for supplier performance evaluation, however the alignment between criteria and indicators is not fully established because the indicators used are more geared to monitoring the operation than the supplier evaluation.
Selection criteria and performance indicators for hiring logistics services: A multiple case study with shippers and 3PL.
Keywords: Logística empresarial - indicadores; critérios de seleção de fornecedores; indicadores de desempenho; seleção de fornecedores; supplier selection criteria; performance indicators; supplier selection; ENGENHARIAS::ENGENHARIA DE PRODUCAO